Direct growth of duel-faceted BiVO4 microcrystals on FTO-coated glass for photoelectrochemical water oxidation - Rahman, Gul; Akhtar, Adil; Khan, Noureen Amir; Chae, Sang Youn; Shah, Anwar Ul Haq Ali; Joo, Oh-shim (ELSEVIER GMBH, 2020)
In this study, we report on the direct growth of duel-faceted BiVO4 microcrystals on fluorine doped tin oxide (FTO) coated glass by simple chemical bath deposition as photoanode material for PEC water oxidation. Crystal growth and particle density were affected by bath temperature; films grown in higher bath temperature (95 degrees C) showed great surface coverage and larger particle sizes, as indicated by scanning electron microscopy (SEM) images. X-ray diffraction (XRD) studies revealed that BiVO4 predominantly occurs in the form of monoclinic scheelite crystal structure in all deposited films. UV-vis spectroscopy and X-ray photoelectron spectroscopy (XPS) investigations confirmed the existence of pure BiVO4. High-temperature treatment of the film was found to improve crystallinity and preferential growth of dual-faceted ((010), (110)) BiVO4 microcrystals. An optimized electrode exhibited excellent PEC water oxidation performance, with 0.78 mA.cm(-2) of photocurrent density at 1.23 V versus a reversible hydrogen electrode (RHE) under standard illumination (100 mW.cm(-2) and AM 1.5), which was increased up to 1.23 mA. cm(-2) before dark current started to flow. The electrode also showed good stability when exposed to longer illumination in a 0.5 M Na2SO4 solution, and n-type character. These findings are thus important for the development of a simple method for synthesis of BiVO4 microcrystals as efficient electrode material for PEC water splitting.